Prediction values of fat-soluble vitamin of growth retardation in children aged 1–6 years - Yan, Qingqing; Zhu, Qingwen; Jiang, Chen; Zhang, Lingli; Xu, Xiaojing (Frontiers in Pediatrics, 2024)
Background Retardation among children is a persistent global health concern. Vitamin deficiency in childhood may contribute to growth retardation; however, its causal effects are not fully understood.Objective Here, we aimed to explore the prediction values of Fat-soluble vitamin levels on GR in children aged 1-6 years.Methods 614 children aged from 1-6 years at Nantong Maternal and Child Care Health Hospital between January 2021 and December 2022 in this retrospective observational study participated in the assessment of developmental status and blood detection of vitamin from peripheral blood (PB). The relationship between vitamin levels and GR was analyzed by Multivariable logistic regression analysis.Developmental assessment results showed that 132 cases from 614 with growth retardation (21.50%). Statistical analysis showed children with GR were more likely to be males (59.45% vs. 40.55%, p=0.191). The age of children with GR was significantly higher than those without GR (p<0.01). Importantly, the levels of various fat-soluble vitamins in GR individuals were significantly lower than those in normal individuals. ROC analysis showed that vitamin E, vitamin A and 25(OH) D3 were less effective in predicting GR model (AUC: 0.87, 0.74, and 0.65,). However, the combination of vitamin E, vitamin A and 25(OH)D3 with age was effective in predicting GR. (AUC: 0.84, 0.77, 0.75).The combination of 25(OH)D3, Vitamin E, Vitamin A with age may have good predictive performance for children GR aged 1-6 years.